2020
DOI: 10.1108/rege-02-2018-0037
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting satisfaction and loyalty to online group buying

Abstract: PurposeIn 2008, a phenomenon emerged in online retail that attracted the attention of many people, creating a new virtual model of commerce. This phenomenon was called online group buying and arrived in Brazil in 2010. The purpose of this study was to identify the factors that affect satisfaction and loyalty to group buying sites.Design/methodology/approachThrough structural equation modeling, the relationships between the attractiveness of discount rates, service quality, popularity, online brand image, antec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 43 publications
(92 reference statements)
3
13
0
4
Order By: Relevance
“…As confirmed in the literature, this is influenced by satisfaction and various quality factors (Brusch et al, 2019). Studies continue to examine the impact of various factors on e-commerce satisfaction and loyalty (Al-dweeri et al, 2019;Faraoni et al, 2018;Garcia et al, 2020). Recent studies suggest that, when a website design can save shoppers time, makes it easy to use, offers information about product variety, and delivers items quickly, customers can become highly satisfied (Brusch et al, 2019;Raman, 2019).…”
Section: Literature Reviewmentioning
confidence: 95%
See 2 more Smart Citations
“…As confirmed in the literature, this is influenced by satisfaction and various quality factors (Brusch et al, 2019). Studies continue to examine the impact of various factors on e-commerce satisfaction and loyalty (Al-dweeri et al, 2019;Faraoni et al, 2018;Garcia et al, 2020). Recent studies suggest that, when a website design can save shoppers time, makes it easy to use, offers information about product variety, and delivers items quickly, customers can become highly satisfied (Brusch et al, 2019;Raman, 2019).…”
Section: Literature Reviewmentioning
confidence: 95%
“…As payments are processed through a debit or credit card in online shopping, consumers also give attention to information about the e-retailer as a source of protection (Vasic et al 2018). Dimensions such as fulfilment, ease of use, reliability, security, and privacy are important for websites that market products that need physical delivery (Yang et al, 2005), and customers' demand for delivery deadlines, security, and reliable e-commerce services is very high (Garcia et al, 2020). Shih (2004) reports a significant and positive impact of website security on users' acceptance of taking online delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, Lazada can pay attention to the pricing provided by each seller. Then further research is suggested to be able to use other variables that can affect customer loyalty, such as Trust Garcia et al (2020) or social media marketing activities Yadav and Rahman (2018). In other words, Lazada's online site is expected to pay attention to factors that can increase its customer loyalty.…”
Section: Discussionmentioning
confidence: 99%
“…Retail loyalty requires the intention of repurchase, obtaining satisfaction as a result. The repurchase or future preference is the need to purchase a product/service again (Garcia, Freire, Santos, & Andrade, 2020).…”
Section: Satisfaction With Quality Attributesmentioning
confidence: 99%